The Economics Spectrum Drives Root Trait Strategies in Mediterranean Vegetation - de la Riva, Enrique G.; Querejeta, José Ignacio; Villar, Rafael; Pérez-Ramos, Ignacio M.; Marañón, Teodoro; Galán Díaz, Javier; de Tomás Marín, Sergio; Prieto, Iván (Frontiers in Plant Science, 2021)
Extensive research efforts are devoted to understand fine root trait variation and to confirm the existence of a belowground root economics spectrum (RES) from acquisitive to conservative root strategies that is analogous to the leaf economics spectrum (LES). The economics spectrum implies a trade-off between maximizing resource acquisition and productivity or maximizing resource conservation and longevity, however, this theoretical framework still remains controversial for roots. We compiled a database of 320 Mediterranean woody and herbaceous species to critically assess if the classic economics spectrum theory can be broadly extended to roots. Fine roots displayed a wide diversity of forms and properties in Mediterranean vegetation, resulting in a multidimensional trait space. The main trend of variation in this multidimensional root space is analogous to the main axis of LES, while the second trend of variation is partially determined by an anatomical trade-off between tissue density and diameter. Specific root area is the main trait explaining species distribution along the RES, regardless of the selected traits. We advocate for the need to unify and standardise the criteria and approaches used within the economics framework between leaves and roots, for the sake of theoretical consistency.